O não-lugar do outro: sistemas migratórios e transformações sociais em Barcarena - HAZEU, Marcel Theodoor (Universidade Federal do Pará, 2017)
This research aimed to examine the possibility of studying social changes in relation to migration systems in the context of the installation and operation of an industrial-port-building complex in Barcarena, in the Amazon. This approach was first applied to a rereading of the social history of the formation of Barcarena, where it came to identify various migration systems that contribute to new interpretations of historical social changes in the city. From the experiences and stories of the residents (collected through semi-structured interviews and participant observation) around the complex, official documents and new produced statistical data were identified four migration systems, defined as “metropolization”, “movement of goods”, “labor mobility” and “forced displacement and ex-re-appropriations”. The analysis of these systems demonstrates strategies behind the social transformations, characterized by the “peripherisation” of the surrounding of the ports and industries and expansion of infrastructure and dynamic logistics for primary processing of ores and the export of a growing range of products. The governmental and business strategies are withdrawal of investments in the communities, the maintenance of permanent threats of expropriation and the subnot-contracting of locals in the industries and ports. Resistances are limited to the disputes on land that is considered of secondary interest to businesses. Barcarena became a global city almost without local interference. Reversing this logic, although necessary, seems to be far away, at this time.